EFEKTIVITAS KOMUNIKASI INTERPERSONAL PADA PRODUK BOUQUET - Dewi Kurnia; Desi Hasbiyah; Ali Alamsyah Kusumadinata (Universitas Djuanda, 2023)
The bouquet trend is being used on graduation day as a symbol of communication. The use of the bouquet requires interpersonal communication so that the meaning of the bouquet as a symbol of communication can be understood, but how does interpersonal communication become effective, so this research aims to provide information on how much influence the effectiveness of interpersonal communication on bouquet products. The research method used in this research is correlational quantitative research method. The research instruments used used questionnaires, interviews and observations. The population in this study were 30th generation graduates at Mathla'ul Anwar University Banten, totaling 560 population and the sample used was 85 respondents using probability sampling technique. The data analysis used is simple linear regression test, determination coefficient test and hypothesis testing. Measurement of the results of this study using a Likert scale with an interpretation assessment using WMS (weight mean score). The results prove that there is a strong and significant influence on the effectiveness of interpersonal communication in bouquet. This is evidenced by the results of statistical tests on simple linear regression analysis resulting in a regression coefficient on the variable (X) of 0.209 stating that every 1% increase will cause an increase in the variable (Y) of 0.209. The regression coefficient is positive, so it can be said that the direction of the influence of variable X on variable Y is positive.